Between the Oche and Treble-Twenty: Darts as a "Way of Life" in Contemporary London. Issue 3 (3rd July 2022) - Howe Bukowski, Nicholas W.
ABSTRACT: This article serves to answer the question, "What sustains the continued relevance of darts for working-class men in postindustrial Britain?" Darts remains a deeply popular activity and increasingly popular spectator sport in contemporary Britain, with common associations with the social clubs, working men's clubs, and pubs of industrial Britain. This article addresses the continued place of darts within the context of the deeply destructive process of structural economic change that has transformed the country's economic, social, and physical landscape and has deeply altered forms of working-class spaces of leisure from pubs to social clubs in long-standing neighborhoods. The author argues that darts is a medium that acts as a form of bridging between the periods of industrial and postindustrial Britain so as to continue working-class modes of socialization and relations that have been altered with the shift to postindustrialism. Darts acts as a mode of orientation and direction—a "way of life"—that mediates and enables a connection between industrial and postindustrial Britain. Moreover, the continuation of playing darts allows for the continuation of spaces of kinship and socialization for working-class men within profound gentrification and the transformation of London into a "Global City" dictated by financial capital. This basis of this article is derived from interviews and observation conducted at a series of amateur darts events across Greater London in January 2016. This article allows for a consideration of the role of leisure and sport within continued institutions and memories of class.